2021
DOI: 10.3390/ijerph18094492
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dog-Assisted Interventions in Higher Education: Students’ Attitudes and Perceived Effects on Well-Being

Abstract: Both, in the transition to university and during it, students experience a multitude of different changes. Thus, it is no surprise that many students in higher education report suffering from mental health problems. To address their concerns, animal-assisted interventions (AAIs) have gained more and more attention over the past few years. Nonetheless, AAIs have neither yet been used nor researched at German universities. Two studies were carried out to address this issue. In Study I, 709 university students an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…42 The final category comprising of students who love dogs, is reflected by the fact majority of the respondents and supporters of a CSP in this study owned dogs and indicated dogs were integral to their lives. The majority of 'dog loving' participant characteristics reported in numerous similar studies elsewhere 10,24,25,30,31,37 strengthens this inference. It likely reflects the psychology of experiencing satisfaction, happiness, and improved well-being as a result of being connected with an object of admiration and adoration 43 ; as well as the mental health, well-being, loneliness reduction, and physical health enhancement effect of giving and receiving affection.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…42 The final category comprising of students who love dogs, is reflected by the fact majority of the respondents and supporters of a CSP in this study owned dogs and indicated dogs were integral to their lives. The majority of 'dog loving' participant characteristics reported in numerous similar studies elsewhere 10,24,25,30,31,37 strengthens this inference. It likely reflects the psychology of experiencing satisfaction, happiness, and improved well-being as a result of being connected with an object of admiration and adoration 43 ; as well as the mental health, well-being, loneliness reduction, and physical health enhancement effect of giving and receiving affection.…”
Section: Discussionsupporting
confidence: 53%
“…These participant characteristics are common in numerous surveys and RCT studies on CSPs in university settings. 10,24,25,[29][30][31]37 Although those who may not be acquainted with dogs may still benefit from CSPs as indicated by a few of the respondents who did not own dogs but still supported it. It emphasises the need for tailored approaches to student support and health promotion in universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study gives voice to university students and recent graduates by helping higher education institutions make informed policy decisions to better support mental health in their student and graduate populations worldwide [ 18 , 19 ]. Our findings advance the application of positive framing and personal resource development as a strategy to protect one’s mental health [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring and comparing the perceptions of recent graduates and current students will inform policy recommendations that support students during their studies and better prepare them for the transition to work. These policies are essential irrespective of COVID-19, with evidenced growth in mental health issues among university students, recent graduates, and youth more generally before the pandemic [ 10 , 18 , 19 ]). Further, a reported rise in unhappiness among UK-based children (aged 10 to 15 years) suggests that more subjective wellbeing-related issues could emerge in higher education institutions in the coming years as individuals transition to tertiary education and, subsequently, the graduate labour market [ 20 ].…”
Section: Introductionmentioning
confidence: 99%